2015
DOI: 10.1038/labinvest.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Decreased proteasomal function accelerates cigarette smoke-induced pulmonary emphysema in mice

Abstract: Chronic obstructive pulmonary disease (COPD) is a disease common in elderly people, characterized by progressive destruction of lung parenchyma and chronic inflammation of the airways. The pathogenesis of COPD remains unclear, but recent studies suggest that oxidative stress-induced apoptosis in alveolar cells contributes to emphysematous lung destruction. The proteasome is a multicatalytic enzyme complex that plays a critical role in proteostasis by rapidly destroying misfolded and modified proteins generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
(77 reference statements)
0
21
0
1
Order By: Relevance
“…Exposure to tobacco and/or e-cig/nicotine vapor elevates oxidative-nitrative stress and inflammation that results in autophagy-flux impairment, further hampering the vital cellular homeostatic processes involved in the clearance of misfolded proteins and bacterial/viral pathogens that eventually impact the cell survival [10, 11, 18, 2325]. Moreover, impaired autophagy flux results in perinuclear aggresome-bodies that are the hallmark of several neurodegenerative and protein-misfolding disorders [2628].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to tobacco and/or e-cig/nicotine vapor elevates oxidative-nitrative stress and inflammation that results in autophagy-flux impairment, further hampering the vital cellular homeostatic processes involved in the clearance of misfolded proteins and bacterial/viral pathogens that eventually impact the cell survival [10, 11, 18, 2325]. Moreover, impaired autophagy flux results in perinuclear aggresome-bodies that are the hallmark of several neurodegenerative and protein-misfolding disorders [2628].…”
Section: Introductionmentioning
confidence: 99%
“…The recent exhaustive studies using variety of pre-clinical models that includes human lung structural cells or tissues have clearly demonstrated that tobacco-smoke impaired-autophagy mediates accumulation of aggresome-bodies, which is primarily a cytoplasmic organelle comprised of aggregated (misfolded or damaged) proteins that initiates chronic inflammatory-apoptotic responses leading to senescence and emphysema progression (Fig. 1a) [10, 11, 17, 18, 20, 22, 25, 29, 30]. The pathogenic role of autophagy-impairment in COPD-emphysema is supported by findings from multiple studies demonstrating the accumulation of ubiquitinated proteins and p62 (an impaired-autophagy marker) that accelerates cellular senescence and COPD-emphysema pathogenesis [10, 11, 17, 18, 20, 22, 25, 29, 30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and mortality rate of COPD keep increasing yearly, with significant impact on the health of people worldwide. Although the pathogenesis of COPD is still not fully understood, a variety of studies have shown that inflammation, oxidative stress, protease/anti-protease imbalance, and apoptosis of lung cells are involved in COPD [1][2][3]. Cigarette smoking is the most important risk factor of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired proteasome function can result in the accumulation of altered proteins, resulting in cellular dysfunction and cell death. Recently, decreased proteasomal function was shown to accelerate cigarette smoke-induced pulmonary emphysema in a mouse model 40. Impaired proteasomal expression might be important in the pathogenesis of emphysema.…”
Section: Discussionmentioning
confidence: 99%